Gastroprotective effect of vitamin U in D‐galactosamine‐induced hepatotoxicity. Issue 9 (6th June 2022) - Topaloglu, Dileknur; Turkyilmaz, Ismet Burcu; Yanardag, Refiye
Abstract: Galactosamine (GalN) is a well‐known agent for inducing viral hepatitis models in rodents, but it can cause toxicity on different organs. Vitamin U (Vit U) has been proved as a powerful antioxidant on many toxicity models. The present study was designed to investigate the protective effects of Vit U on GalN‐induced stomach injury. Rats were divided into four groups as follows: control (group I), Vit U given animals (50 mg/kg per day; group II), GalN administered animals (500 mg/kg at a single dose; group III), GalN + Vit U given animals (at the same dose and time, group IV). At the end of the 3rd day, animals were killed, and stomach tissues were taken. They were homogenized and centrifuged. In comparison to the control group, glutathione, total antioxidant capacity levels, catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase, glutathione‐S‐transferase, and Na + /K + ‐ATPase activities of GalN group were found to be decreased. On the contrary, lipid peroxidation, advanced oxidized protein products, hexose‐hexosamine, fucose, sialic acid, reactive oxygen species levels, as well as the activities of myeloperoxidase, xanthine oxidase, and lactate dehydrogenase were elevated. Administration of Vit U reversed these abnormalities in the GalN group. It can be concluded that Vit U exerts its unique antioxidant effect and prevents GalN‐induced gastric damage.